Molecular detection and identification of group 16SrV and 16SrXII phytoplasma associated with potatoes in Colombia - Mejía, Juan Fernando; Contaldo, N.; Paltrinieri, S; Pardo, Juan Manuel; Ríos, C.A.; Álvarez, E.; Bertaccini, A (2011)
A severe disease was observed in the potato variety Criolla Colombiana . Main symptomatology consisted of discoloration or yellowing of the whole plant, apical leafroll, dwarfing, axillary buds and thicker internodes. Phytoplasmas related to 16SrV and 16SrXII groups were identified by nested PCR assays followed by real and virtual RFLP and sequence analyses. This is the first report of phytoplasma presence in potato in Colombia and the first identification of group 16SrV phytoplasmas in this crop.